Enriching Kademlia by Partitioning - Monteiro, João (2022)
Experiments presented in this paper were carried out using the Grid'5000 testbed, supported by a scientific interest group hosted by Inria and including CNRS, RENATER and several Universities as well as other organizations (see https://www.grid5000.fr). Publisher Copyright: © 2022 IEEE.